1986
DOI: 10.1093/nar/14.16.6735
|View full text |Cite
|
Sign up to set email alerts
|

O4-Methyldeoxythymidine replacing deoxythymidine in poly[d(A—T)] renders the polymer resistant to the 3′ → 5′ exonuclease activity of the Klenow and T4DNA polymerases

Abstract: We previously reported that O4-alkyl dTTPs could replace, for short times, dTTP in polymer synthesis [Singer et al., PNAS 83, 26-32, 1986]. The reasons for such early termination of synthesis could be either proofreading or the eventual formation of weakly paired primer termini. Utilizing the known 3'----5' exonucleolytic activity of polymerases, in the absence of dNTPs, enabled us to conclude that, in contrast to the digestibility of poly[d(A-T)] which yielded the expected 3'-mononucleotides, the polymerizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The relative ease with which the m4G-T mispair can be extended suggests that it is not a good substrate for proofreading by the "weak" 3'-exonuclease activity of the Klenow fragment. In the absence of any dNTP the exonuclease activity of the Klenow fragment did not excise even m4T-A pairs (Singer, 1986). For the case of another modified base pair, m6G-T, we also found that it was extended much more rapidly to the next template site than the parent G-T base pair (Singer et al, 1989b).…”
Section: Resultsmentioning
confidence: 72%
“…The relative ease with which the m4G-T mispair can be extended suggests that it is not a good substrate for proofreading by the "weak" 3'-exonuclease activity of the Klenow fragment. In the absence of any dNTP the exonuclease activity of the Klenow fragment did not excise even m4T-A pairs (Singer, 1986). For the case of another modified base pair, m6G-T, we also found that it was extended much more rapidly to the next template site than the parent G-T base pair (Singer et al, 1989b).…”
Section: Resultsmentioning
confidence: 72%
“…It is generally assumed that nucleobase analogs can cause replicational errors. Studies with procaryotic polymerases on the incorporation of nucleotide analogs into DNA in vitro have been carried out in many laboratories (12,17,22,26,27,31,34). In contrast, there are only a few reports regarding the utilization of base analogs by eucaryotic DNA polymerases (10,11,33).…”
mentioning
confidence: 99%